Superstrong graphite and preparation method thereof
Through high-pressure sintering and doping sulfur powder, the application limitations of traditional graphite materials under high strength and high pressure are solved, and the mechanical properties and yield of graphite materials are significantly improved.
Patent Information
- Application Number
- CN202510077141.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional graphite materials have limitations in application in high strength, high pressure and harsh environments, and are difficult to meet the needs of complex conditions such as high load, high impact, and wear resistance, mainly due to porosity and grain size problems.
High-pressure sintering technology is adopted to combine the strategy of refining particle size and doping a small amount of sulfur powder, and through a single calcination graphitization treatment, the porosity and grain size of graphite are reduced and its mechanical properties are improved.
The mechanical properties of graphite materials are significantly improved, including flexural resistance, compressive resistance and tensile strength, and the preparation process is simple and the yield is high.
Smart Images

Figure CN119684001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon materials, relates to super-strong graphite materials, and particularly relates to super-strong graphite and a preparation method thereof. Background Art
[0002] As an important non-metallic material, graphite is widely used in many fields such as batteries, electronics, metallurgy, machinery, aerospace, etc. due to its excellent electrical conductivity, thermal conductivity, high temperature resistance and lubricity. However, the application of traditional graphite in high-strength, high-pressure and harsh environments has certain limitations. Especially in the fields of aerospace, automobiles, metallurgy, etc., the strength and stability of materials are extremely strict. Traditional graphite often cannot meet the needs of complex conditions such as high load, high impact, and wear resistance in these applications.
[0003] High-strength graphite is a graphite material that significantly improves its mechanical strength, compressive properties, corrosion resistance and thermal stability by optimizing the structure of graphite, introducing high-density technology or compounding with other materials. Compared with traditional graphite, high-strength graphite has stronger mechanical properties and wider application prospects, showing its unique advantages in many fields.
[0004] Due to its layered structure, low density, thermal expansion characteristics, purity issues and other factors, it is difficult to prepare high-strength graphite materials using traditional preparation methods. Pores and grain size directly affect the mechanical properties of graphite materials, especially strength. The presence of pores makes graphite prone to crack propagation when subjected to external forces, while larger grain sizes may lead to uneven mechanical properties of graphite.
[0005] The applicant has found through research that high-pressure sintering can effectively reduce the porosity in graphite. However, the high-temperature and high-pressure environment easily promotes the growth of grains. Especially when sintered for a long time or at too high a temperature, the grain size of graphite particles tends to increase, affecting its mechanical properties. Oversized grains will increase the brittleness of graphite and reduce the strength of graphite materials. Therefore, how to reduce the porosity of graphite while reducing its grain size is a technical problem that those skilled in the art hope to solve in preparing super-strong graphite. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a super strong graphite and a preparation method thereof. The present invention can obtain super strong graphite by one-time calcination and graphitization, has a simple preparation process, and can reduce the pores of graphite while reducing its grain size, so that the obtained super strong graphite has good mechanical properties.
[0007] The technical solution of the present invention is achieved in this way:
[0008] A method for preparing super graphite specifically comprises the following steps:
[0009] (1) adding sulfur powder to green coke powder with a D50 of 0.1 to 5 μm, dispersing the powder evenly to obtain a mixed powder, and then pressing the mixed powder into a green body;
[0010] (2) placing the green body in a pressure sintering furnace and sintering at 1 to 5 MPa to obtain a sintered block;
[0011] (3) The calcined block is graphitized to obtain the super strong graphite.
[0012] Furthermore, the raw coke powder is one or both of raw petroleum coke and raw asphalt coke.
[0013] Furthermore, the mass of the sulfur powder accounts for 0.1-3% of the total mass of the mixed powder. Preferably, 1.0-2.5%. Studies have shown that when the amount of sulfur powder is too much, it will cause cracking of the roasted block and affect the product yield; when the mass proportion of sulfur powder is 1.0-2.5%, the obtained super graphite has a smaller grain size and open porosity, and the mechanical properties are the best.
[0014] Furthermore, the raw coke powder is obtained by air jet milling, and the D50 of the raw coke powder is 2 μm.
[0015] Furthermore, in step (1), the specific steps of compression molding are: first, the raw coke powder is pre-molded on a flat vulcanizer using a pressure of 1 to 15 MPa for 10 to 30 seconds, then the green coke powder is pressed at a pressure of 150 to 250 MPa for 10 to 20 minutes by a cooling press, and then the green body is left for more than 12 hours to obtain the green body.
[0016] Furthermore, during the calcination in step (2), the temperature is raised to 800-1200° C. at a heating rate of 0.1-0.3° C. / min under the protection of an inert gas, maintained at that temperature for 2-6 hours, and then cooled to room temperature.
[0017] Furthermore, the heating rate is 0.2°C / min.
[0018] Furthermore, during sintering, the pressure in the pressure sintering furnace is 3 MPa.
[0019] Furthermore, in step (3), the specific steps of graphitization treatment are: raising the temperature of the calcined block to 2200-2800°C at a heating rate of 0.5-4°C / min under the protection of inert gas, and keeping it warm for 0.5-4h, then cooling it to below 200°C at a cooling rate of 0.5-4°C / min, and then naturally cooling it to room temperature.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention combines the strategies of particle size refinement, pressure sintering and doping with sulfur powder to significantly reduce the porosity and grain size of graphite materials and improve the mechanical properties of graphite materials. Specifically, low-particle coke powder can reduce porosity and increase the bonding strength of carbonaceous interfaces, thereby obtaining a denser block, but it also increases the risk of cracking. The present invention combines a suitable heating rate and sintering pressure to avoid cracking of the carbon block obtained by sintering, effectively improving the yield rate; high-pressure sintering can promote the graphite particles to be more closely combined, reduce the formation of pores, and further increase the density of graphite materials; and the addition of a small amount of sulfur powder will enrich the grain boundaries under high temperature conditions, by reducing the grain boundary energy, stabilizing the grain boundary structure, and inhibiting the migration of grain boundaries, thereby hindering the excessive growth of grains, promoting the formation of fine grains, and increasing the number of interfaces between grains; in addition, sulfur powder can also form weak chemical bonds at the grain boundaries of graphite or generate sulfide particles by combining with carbon and impurities, producing a "pinning" effect on the grain boundaries and enhancing the bonding force between grains. The above effects work together to achieve the densification and strengthening of graphite, thereby reducing the pores of graphite and its grain size, which can significantly improve the mechanical properties of super-strong graphite.
[0022] 2. The present invention prepares the graphite material by one-time calcination graphitization, the preparation process is simple, and the prepared graphite material has extremely high strength: the flexural strength reaches 153.7MPa, the compressive strength reaches 210.8MPa, the tensile strength reaches 100.2MPa, and has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 - Comparison of open porosity and grain size Lc of graphite blocks prepared in Example 1 and Comparative Examples 2 to 6.
[0024] Figure 2 - Comparison diagrams of stress-strain curves of bending, compression and tension of graphite blocks prepared in Example 1 and Comparative Examples 2 to 6 (ac) and corresponding strength comparison diagrams (df).
[0025] Figure 3 - SEM images of graphite blocks prepared in Example 1 and Comparative Examples 2 to 6. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0027] Example 1
[0028] A method for preparing super graphite specifically comprises the following steps:
[0029] (1) Raw petroleum coke doped with 2% sulfur powder and having an average particle size of 2 μm is molded in a flat vulcanizer at a pressure of 3 MPa, and then the block is isostatically pressed at 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0030] (2) The green block obtained in (1) was placed in a pressure calcining furnace. In a nitrogen atmosphere of 3 MPa, the temperature was raised to 1050°C at a rate of 0.2°C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200°C at a rate of 0.1°C / min, and then naturally cooled to room temperature to obtain a calcined block.
[0031] (3) The calcined block prepared in step (2) is heated to 2400°C at a heating rate of 0.5°C / min under argon protection, and kept at this temperature for 1 hour, then cooled to below 200°C at a cooling rate of 0.5°C / min, and then naturally cooled to room temperature to obtain the super strong graphite block, named SG-SP2.
[0032] Comparative Example 1
[0033] A method for preparing super graphite specifically comprises the following steps:
[0034] (1) Raw petroleum coke with an average particle size of 2 μm is molded in a flat vulcanizer at a pressure of 3 MPa, and then the block is isostatically pressed at 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0035] (2) The green block obtained in (1) was placed in a pressure calcining furnace. In a nitrogen atmosphere of 3 MPa, the temperature was raised to 1050°C at a rate of 0.2°C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200°C at a rate of 0.1°C / min, and then naturally cooled to room temperature to obtain a calcined block.
[0036] (3) The calcined block prepared in step (2) is heated to 2400°C at a heating rate of 0.5°C / min under argon protection, and kept at this temperature for 1 hour, then cooled to below 200°C at a cooling rate of 0.5°C / min, and then naturally cooled to room temperature to obtain the high-strength graphite block, named SG-P2.
[0037] Comparative Example 2
[0038] A method for preparing super graphite specifically comprises the following steps:
[0039] (1) Raw petroleum coke doped with 2% sulfur powder and having an average particle size of 2 μm was molded in a flat vulcanizer at a pressure of 3 MPa, and then the block was isostatically pressed at 200 MPa for 10 minutes and left for more than 12 hours to obtain a green body.
[0040] (2) The green blocks obtained in (1) are placed in a conventional box-type five-sided furnace sagger, and the remaining space is filled with burial material.
[0041] (3) placing the prepared sagger in step (2) in a five-sided furnace, and under nitrogen protection, raising the temperature to 1050°C at a heating rate of 0.2°C / min, and keeping the temperature for 4 hours, then cooling the temperature to below 200°C at a cooling rate of 0.1°C / min, and then naturally cooling to room temperature to obtain a calcined block.
[0042] (3) The calcined block prepared in step (2) is heated to 2400° C. at a heating rate of 0.5° C. / min under argon protection, and kept at this temperature for 1 h, then cooled to below 200° C. at a cooling rate of 0.5° C. / min, and then naturally cooled to room temperature to obtain the graphite block, named SG-S2.
[0043] Comparative Example 3
[0044] A method for preparing super graphite specifically comprises the following steps:
[0045] (1) Raw petroleum coke doped with 2% sulfur powder and having an average particle size of 6 μm was molded in a flat vulcanizer at a pressure of 3 MPa, and then the block was isostatically pressed at 200 MPa for 10 minutes and left for more than 12 hours to obtain a green body.
[0046] (2) The green block obtained in (1) was placed in a pressure calcining furnace. In a nitrogen atmosphere of 3 MPa, the temperature was raised to 1050°C at a rate of 0.2°C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200°C at a rate of 0.1°C / min, and then naturally cooled to room temperature to obtain a calcined block.
[0047] (3) The calcined block prepared in step (2) is heated to 2400° C. at a heating rate of 0.5° C. / min under argon protection, and kept at this temperature for 1 h, then cooled to below 200° C. at a cooling rate of 0.5° C. / min, and then naturally cooled to room temperature to obtain the graphite block, named SG-SP6.
[0048] Comparative Example 4
[0049] A method for preparing super graphite specifically comprises the following steps:
[0050] (1) A raw petroleum coke doped with 2% sulfur powder and having an average particle size of 6 μm is molded in a flat vulcanizer at a pressure of 3 MPa, and then the block is isostatically pressed at 200 MPa for 10 min. The block is left for more than 12 h to obtain a green body.
[0051] (2) The green blocks obtained in (1) are placed in a conventional box-type five-sided furnace sagger, and the remaining space is filled with burial material.
[0052] (3) placing the prepared sagger in step (2) in a five-sided furnace, and under nitrogen protection, raising the temperature to 1050°C at a heating rate of 0.2°C / min, and keeping the temperature for 4 hours, then cooling the temperature to below 200°C at a cooling rate of 0.1°C / min, and then naturally cooling to room temperature to obtain a calcined block.
[0053] (3) The calcined block prepared in step (2) is heated to 2400° C. at a heating rate of 0.5° C. / min under argon protection, and kept at this temperature for 1 h, then cooled to below 200° C. at a cooling rate of 0.5° C. / min, and then naturally cooled to room temperature to obtain the graphite block, named SG-S6.
[0054] Comparative Example 5
[0055] A method for preparing super graphite specifically comprises the following steps:
[0056] (1) Raw petroleum coke doped with 2% sulfur powder and having an average particle size of 13 μm was molded in a flat vulcanizer at a pressure of 3 MPa, and then the block was isostatically pressed at 200 MPa for 10 minutes and left for more than 12 hours to obtain a green body.
[0057] (2) The green block obtained in (1) was placed in a pressure calcining furnace. In a nitrogen atmosphere of 3 MPa, the temperature was raised to 1050°C at a rate of 0.2°C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200°C at a rate of 0.1°C / min, and then naturally cooled to room temperature to obtain a calcined block.
[0058] (3) The calcined block prepared in step (2) is heated to 2400° C. at a heating rate of 0.5° C. / min under argon protection, and kept at this temperature for 1 h, then cooled to below 200° C. at a cooling rate of 0.5° C. / min, and then naturally cooled to room temperature to obtain the graphite block, which is named SG-SP13.
[0059] Comparative Example 6
[0060] A method for preparing super graphite specifically comprises the following steps:
[0061] (1) A raw petroleum coke with a particle size of 13 μm and doped with 2% sulfur powder is formed in a flat vulcanizer at a pressure of 3 MPa, and then the block is isostatically pressed at 200 MPa for 10 minutes and left for more than 12 hours to obtain a green body.
[0062] (2) The green blocks obtained in (1) are placed in a conventional box-type five-sided furnace sagger, and the remaining space is filled with burial material.
[0063] (3) placing the prepared sagger in step (2) in a five-sided furnace, and under nitrogen protection, raising the temperature to 1050°C at a heating rate of 0.2°C / min, and keeping the temperature for 4 hours, then cooling the temperature to below 200°C at a cooling rate of 0.1°C / min, and then naturally cooling to room temperature to obtain a calcined block.
[0064] (3) The calcined block prepared in step (2) is heated to 2400° C. at a heating rate of 0.5° C. / min under argon protection, and kept at this temperature for 1 h, then cooled to below 200° C. at a cooling rate of 0.5° C. / min, and then naturally cooled to room temperature to obtain the graphite block, named SG-S13.
[0065] Comparative Example 7
[0066] A method for preparing graphite, comprising the following steps:
[0067] (1) Raw petroleum coke doped with 5% sulfur powder and having an average particle size of 2 μm is molded in a flat vulcanizer at a pressure of 3 MPa, and then the block is isostatically pressed at 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0068] (2) The green block obtained in (1) was placed in a pressure calcining furnace. In a nitrogen atmosphere of 3 MPa, the temperature was raised to 1050°C at a rate of 0.2°C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200°C at a rate of 0.1°C / min, and then naturally cooled to room temperature to obtain cracking of the calcined block.
[0069] Comparative Example 8
[0070] A method for preparing a graphite material comprises the following steps:
[0071] (1) Raw petroleum coke doped with 2% sulfur powder and having an average particle size of 2 μm is molded in a flat vulcanizer at a pressure of 3 MPa, and then the block is isostatically pressed at 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0072] (2) The green block obtained in (1) was placed in a pressure calcining furnace. In a nitrogen atmosphere of 6 MPa, the temperature was raised to 1050°C at a rate of 0.2°C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200°C at a rate of 0.1°C / min, and then naturally cooled to room temperature to obtain cracking of the calcined block.
[0073] 1. The basic properties of the above graphite blocks were tested, among which Shore hardness, resistivity, volume density, flexural strength and compressive strength were tested in accordance with the national standard test method, and the tensile strength was tested by proportionally reducing the dog-bone tensile specimen of the international standard, and the grain size Lc was calculated by the Scherrer formula based on the XRD data. The basic performance parameters are shown in Table 1.
[0074] Table 1. Basic performance parameters
[0075] Performance parameters SG-SP2 SG-P2 SG-S2 SG-SP6 SG-S6 SG-SP13 SG-S13 <![CDATA[Green density (g / cm 3 )]]> 1.25 1.25 1.25 1.22 1.22 1.19 1.19 <![CDATA[Graphite block density (g / cm 3 )]]> 1.96 1.91 1.70 1.79 1.42 1.65 1.33 Mass loss rate (%) 18.68 17.98 19.69 17.80 19.27 16.18 18.04 Volume shrinkage (%) 48.04 46.14 41.13 43.95 30.60 39.46 26.49 Open porosity (%) 0.49 2.55 3.96 15.78 28.96 23.53 39.07 Resistivity (μΩ·m) 14.87 15.70 21.08 17.45 43.3 19.74 64.81 Lc(nm) 20.57 22.28 24.58 31.34 33.02 32.29 33.67 Flexural strength(MPa) 153.7 131.8 72.7 63.0 13.5 25.5 3.6 Compressive strength(MPa) 210.8 182.0 125.0 87.2 28.9 42.2 10.5 Tensile strength(MPa) 102.6 86.5 54.0 30.4 5.3 12.1 3.8 Shore hardness (HSD) 87.5 83.5 76.0 62.7 49.3 51.2 40.5
[0076] As can be seen from the above table, the graphite block SG-SP2 prepared by the present invention using the strategy of pressurized calcination, introduction of impurity sulfur and refinement of raw coke particle size has obvious performance advantages, and the density of graphitized graphite after one calcination can reach 1.96g / cm 3 The volume shrinkage rate is as high as 48.04%, the mass loss rate is only 18.69%, the grain size is only 20.57nm, and the open porosity is only 0.49%; while the density of the graphite block with only sulfur powder is only 1.70g / cm 3 The mass loss rate is only 17.98%, the volume shrinkage rate is 41.13%, and the grain size is 24.58nm; while the density of the graphite block that is only pressurized and calcined without sulfur doping can reach 1.91g / cm 3 The mass loss rate is only 19.69%, the volume shrinkage rate is 46.14%, and the grain size is 22.28nm, which shows that pressure sintering can reduce mass loss and increase volume shrinkage, while the large mass loss of SG-SP2 is mainly due to the volatilization of sulfur. And sulfur doping can only play a significant role in refining grains under pressure sintering.
[0077] 2. The comparison of the open porosity and grain size Lc of the graphite blocks obtained in Example 1 and Comparative Examples 2 to 6 is shown in the figure below: Figure 1 As shown, Figure 1 a is the comparison of open porosity, Figure 1 b is the comparison of grain size Lc. It can be seen from the figure that with the decrease of the average particle size, the open porosity and grain size of the graphite block can be effectively reduced. At the same time, pressure roasting can further reduce the open porosity and grain size of the graphite block. Compared with Comparative Example 6, Example 1 adopts the strategy of refining the particle size, doping with sulfur and pressure roasting to reduce the open porosity of the graphite block by 95.75% and the grain size by 38.91%.
[0078] 3. The stress-strain curves of the graphite blocks obtained in Example 1 and Comparative Examples 2 to 6 for bending, compression and tension and the corresponding strength comparison diagrams are shown in FIG. Figure 2As shown in the figure, it can be seen intuitively that, compared with Comparative Example 6, Example 1 adopts the strategy of refining particle size, sulfur doping and pressure calcination to increase the flexural, compressive and tensile strengths of the graphite block by about 42 times, 19 times and 26 times respectively.
[0079] 4. The SEM images of the graphite blocks obtained in Example 1 and Comparative Examples 2 to 6 are as follows: Figure 3 As shown, the strategy of particle size refinement, sulfur doping and pressure calcination adopted in Example 1 can significantly reduce the porosity of graphite and improve the density.
[0080] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing super strong graphite, characterized in that: The specific steps include: (1) Sulfur powder is added to green coke powder with a D50 of 0.1-5 μm, and the mixture is uniformly dispersed to obtain a mixed powder, and then the mixed powder is pressed into a green body; (2) placing the green body in a pressure sintering furnace and sintering it at 1-5 MPa to obtain a sintered block; (3) The calcined block is graphitized to obtain the super strong graphite.
2. The method for preparing super strong graphite according to claim 1, characterized in that: The raw coke powder is one or both of raw petroleum coke and raw asphalt coke.
3. A method for preparing super strong graphite according to claim 1 or 2, characterized in that: The mass of sulfur powder accounts for 0.1~3% of the total mass of the mixed powder.
4. The method for preparing super strong graphite according to claim 1, characterized in that: The raw coke powder is obtained by air jet milling, and the D50 of the raw coke powder is 2 μm.
5. The method for preparing super strong graphite according to claim 1, characterized in that: In step (1), the specific steps of compression molding are: first, the green coke powder is pre-molded on a flat vulcanizer using a pressure of 1-15 MPa for 10-30 seconds, then the green coke powder is pre-molded on a cool press at a pressure of 150-250 MPa for 10-20 minutes, and then the green body is left for more than 12 hours to obtain the green body.
6. The method for preparing super strong graphite according to claim 1, characterized in that: During the calcination in step (2), the temperature is raised to 800-1200°C at a heating rate of 0.1-0.3°C / min under the protection of an inert gas, and kept at that temperature for 2-6 hours, and then cooled to room temperature.
7. The method for preparing super strong graphite according to claim 6, characterized in that: The heating rate is 0.2 °C / min.
8. The method for preparing super strong graphite according to claim 1, characterized in that: During sintering, the pressure in the pressurized sintering furnace is 3MPa.
9. The method for preparing super strong graphite according to claim 1, characterized in that: In step (3), the specific steps of graphitization treatment are: raising the temperature of the calcined block to 2200~2800°C at a heating rate of 0.5~4°C / min under the protection of inert gas, and keeping it at that temperature for 0.5~4 h, then cooling it to below 200°C at a cooling rate of 0.5~4°C / min, and then naturally cooling it to room temperature.
10. A super strong graphite, characterized in that: The super strong graphite is prepared by the method for preparing the super strong graphite according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of graphite material with low porosity and high bending strength
CN121591502A